Soil health and management matters: A survey of field tree nursery producers. (1st April 2023) - McGrath, Darby; Plummer, Ryan; Williams, Charlene; McGlynn, Bridget
Abstract: Extensive calls for increased tree planning worldwide are highlighting the need for management changes in the field tree nursery sector. Healthy soil is the foundation for sustainable agricultural systems, and best practices for soil management confer tangible benefits to producers as well as broader system-wide benefits. However, field tree producers lack the foundational resources needed to implement, manage, and evaluate soil health practices within their operations. Furthermore, tree producers are unique in that their primary product is central to the sustainable development of urban spaces and are facing increased demand for high-quality trees. There is subsequently a two-pronged need. First, a greater understanding of the key objectives, opportunities, and challenges driving soil management in tree production is required to support the development of specified practices, within the sector. Second, a greater characterization of the short- and long-term value of trees is required to incentivize the soil health practices that will support resilience in tree production systems. The study characterizes the soil health and management practices implemented in Ontario by field tree nursery producers. A questionnaire was administered in the summer of 2020 to Ontario tree nursery producers within the Landscape Ontario Horticultural Trades Association (N = 29). Responding producers provided insight into soil management practices, opportunities and challenges. Tree nursery producers expressed a need for resources to support cover crop usage and comprehensive soil testing to improve tree performance. Reflection on current soil management challenges and opportunities highlights the benefits of considering soil management as one aspect within the broader social-ecological system. Highlights: Field tree producers lack the foundational resources needed to implement, manage, and evaluate soil health within their operations. Tree producers are unique in that their primary product, namely high-quality trees, is central to the sustainable development of urban spaces. Tree producers identified improved tree performance and increased soil organic matter as key objectives that could drive industry level change. Tree producers expressed a need for resources to support use of cover crops and more comprehensive soil testing. Characterization of the value of trees is required to incentivize soil health practices that support resilience in tree production systems.